The effects of state-sponsored merit scholarships on course selection and major choice in college - Christopher Mark Cornwell; Kyung Hee Lee; David B. Mustard (Institute for the Study of Labor (IZA), 2006)
A common justification for HOPE-style merit-aid programs is to promote and reward academic achievement, thereby inducing greater investments in human capital. However, grade-based eligibility and retention rules encourage other behavioral responses. Using data extracted from the longitudinal records of all undergraduates who enrolled at the University of Georgia (UGA) between 1989 and 1997, we estimate the effects of HOPE on college GPA, course selection, and major choice, treating non-residents as a control group. First, we find that HOPE increased resident freshman GPA by 0.13 point, while its effect on GPA after the first year is weak. Second, HOPE reduced the number of credit hours completed in math and science core curriculum courses during the first year, and this effect persisted into the second at roughly the same magnitude. Over both years, the estimated program effects imply that residents completed about 1.2 fewer math and sciences credit hours. Finally, the likelihood that the average resident freshman would choose to major in Education jumped 1.2 percentage points relative to their out-of-state counterparts after HOPE was introduced and the scholarship's influence on this decision was more pronounced for women and whites.
Keywords: I2; 330; merit aid; education finance